The science and physiology of flexibility and stretching implications and applications in sport performance and health - Behm, David G. PhD (Routledge, 2019)
Stretching is a fundamentally important part of sport and exercise, playing a role in improving performance, and preventing injury and rehabilitation, but its scientific underpinnings have, to this point, been overlooked in book publishing. The Science and Physiology of Flexibility and Stretching is the most up-to-date and comprehensive book to cover the underlying physiology and psychology of stretching, critically assessing why, when, and how we should stretch, as well as offering a highly illustrated, practical guide to stretching exercises. Placing stretching in the context of both health and performance, the first section of the book sets out the science behind stretching, critically assessing the benefits, disadvantages, and roles of different types of stretching, exploring the mechanism behind increasing range-of-movement through stretching and other methods, and offering evidence-based guidance on building stretching into warm-ups. In its second section, the book provides a step-by-step guide to static, dynamic, and PNF stretching exercises for beginners, through recreational athletes, to elite performers. Richly Illustrated, and including an online resource, The Science and Physiology of Flexibility and Stretching provides an important scientific enquiry into stretching, and an invaluable reference for any strength and conditioning coach or student, personal trainer, sports coach, or exercise scientist